Obsidian conveyance and late prehistoric hunter-gatherer mobility as seen from the high Wind River Range, Western Wyoming. (2nd July 2016) - Morgan, Christopher; Harvey, David C.; Trout, Lukas
Abstract : Sampling 16 of 52 house features at High Rise Village (HRV; 48FR5891), a large residential locus at 3, 273 m (10, 720 ft) elevation in Wyoming's Wind River Range produced 25 AMS dates, 23 diagnostic projectile points, 148 obsidian artifacts (mostly retouch debris) as well as abundant chert debitage, small quantities of faunal bone, and groundstone milling equipment. Based on AMS, projectile point, and obsidian hydration data, the site's lodges appear to have been occupied on a sporadic basis mainly between 2, 300 and 850 cal BP. Source provenance determination made via X-ray fluorescence spectrometry indicates that most of the obsidian at the site originated in Jackson Hole and secondarily is from Yellowstone Plateau sources, suggesting a Late Prehistoric residentially-mobile, seasonal, and elevationally transhumant settlement system focused on the Jackson Hole area. GIS-based assessments of the costs of procuring the obsidian found at HRV suggests, however, that though economic considerations certainly played a principal role in determining obsidian conveyance decisions, other factors such as social or cultural dynamics may have conditioned the preference for Yellowstone sources over eastern Idaho sources, ultimately suggesting that social boundaries played a role in generating the different toolstone conveyance zones seen in the region during the Late Prehistoric.